Life Experience of Chronic Kidney Diseases Undergoing Hemodialysis Therapy - Pipit Festi Wiliyanarti; Abd Muhith (NurseLine Journal, 2019)
The incident of Kidney Disease increased year by years. Hemodialysis treatment is one of supportive therapies that can be maintained in health conditions of the chronocal kidney disease patient. This therapy can not replace the fuction of the kidney, however it could manage the quality of life of the kidney disease patients. The research descriptive qualitative approach was used in this study. The research results found 5 themes about chronic kidney disease patients with hemodyalisis. Those five themes were the knowledge of hemodynamic therapy, the impact of hemodynamic therapy, patients coping during the treatment process, family support and chronic kidney disease with hemodynamic therapy.